2024
DOI: 10.1371/journal.pone.0297120
|View full text |Cite
|
Sign up to set email alerts
|

Human error risk prioritization in crane operations based on CPT and ICWGT

Aihua Li

Abstract: Human error plays a significant role in crane safety. To increase the accuracy and rationality of human error risk prioritization for crane operations, this study proposes a risk prioritization model for human errors in crane operations based on the cumulative prospect theory (CPT) and the improved combination weighting model of game theory (ICWGT). The ICWGT integrates the risk-factor weights obtained via subjective and objective methods. Trapezoidal fuzzy numbers are used to describe experts’ uncertainty inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…To address this issue, Li and Zhao [12] proposed a model for crane safety assessment that integrates CPT and entropy. Li [4] proposed a risk prioritization model for human errors in crane operations based on CPT and an improved combination weighting model based on game theory. Thus, in the present study, CPT was utilized to consider the psychological behavior of decision makers in crane hazard assessment.…”
Section: Literature Review On Crane Safety Evaluationmentioning
confidence: 99%
See 2 more Smart Citations
“…To address this issue, Li and Zhao [12] proposed a model for crane safety assessment that integrates CPT and entropy. Li [4] proposed a risk prioritization model for human errors in crane operations based on CPT and an improved combination weighting model based on game theory. Thus, in the present study, CPT was utilized to consider the psychological behavior of decision makers in crane hazard assessment.…”
Section: Literature Review On Crane Safety Evaluationmentioning
confidence: 99%
“…Research has highlighted the role of linguistic information in the assessment of crane operational risks [4]. Various techniques for uncertain linguistic representations have been applied to safety assessments of cranes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Das et al [ 40 ] identified and ranked the potential failures of crane operations using the Z number in conjunction with the fuzzy VIKOR. To reflect the risk attitudes of experts and integrate subjective and objective weights, Li [ 41 ] proposed an improved FMEA method for human errors in crane operations by using cumulative prospect theory and improved combination weighting model of game theory. Although numerous studies have been conducted on FMEA using various approaches that integrate decision support techniques, there is a scarcity of research on the assessment of crane risks through the integration of MCDM with FMEA.…”
Section: Introductionmentioning
confidence: 99%